PENGARUH SENSITIVITY TO MARKET RISK, KUALITAS ASET, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN FARMASI SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mutia; Muhammad Salman; Agustina Nurul Fajriah (Jurnal Mahasiswa Akuntansi Samudra, 2026)
This study aims to determine the effect of sensitivity to market risk, asset quality, and liquidity on the financial performance of Sharia pharmaceutical companies. This research adopts a quantitative approach. The sampling technique used is purposive sampling, with a total of seven companies selected as the research sample. The partial test results indicate that sensitivity to market risk has no significant effect on financial performance, as evidenced by a significance value of 0.565 > 0.05. Similarly, asset quality shows no significant effect on financial performance, with a significance value of 0.118 > 0.05. Meanwhile, liquidity has a significant positive effect on financial performance, with a significance value of 0.000 < 0.05. The F-test results show that sensitivity to market risk, asset quality, and liquidity simultaneously have a significant effect on financial performance, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) obtained is 52%, indicating that the three independent variables collectively explain 52% of the variation in financial performance. This study has several limitations, including variable measurement, research period, and industrial scope.